Effect of fluorination on the phase sequence, dielectric and electro-optical properties of ferroelectric and antiferroelectric mixtures. Issue 14 (8th December 2017) - Debnath, Asim; Mandal, Pradip Kumar
ABSTRACT: Four multicomponent room temperature mixtures were formulated using a pyrimidine-based achiral matrix as host and four terphenyl-based ester chiral compounds as dopants. Among the four mixtures, two exhibit antiferroelectric and two other exhibit ferroelectric phases at room temperature. Dopant molecules differ from each other by position and number of fluorine atom substitution at the benzoate group of the molecular rigid core. Number and location of fluorine atoms in the dopant structure show significant effect on the phase sequences as well as on different physical properties. All the mixtures found to have moderate spontaneous polarisation, high tilt angle, very fast switching time and low viscosity which are important for liquid crystal-based display applications. Graphical Abstract: